Effects of two different angiotensin receptor blockers on blood glucose level and HbA1c in type-2 diabetes mellitus patients with hypertension - Shafat Iqbal Bhati; S. F. Haque; S. S. Siddiqi; Rizwan Ahmad (SpringerOpen, 2023)
Abstract Diabetes mellitus is a common metabolic disorder characterized by chronic hyperglycemia and disturbance of carbohydrate, fats, and protein metabolism. Type 2 diabetes mellitus results from reduced insulin secretion, decreased glucose utilization, and increased glucose production, which results in hyperglycemia. Hypertension further increases the risk of cardiovascular diseases, including coronary heart disease (CHD), congestive heart failure (CHF), ischemic and hemorrhagic stroke, renal failure, and peripheral arterial disease (PAD). Angiotensin receptor blockers (ARBs) are very effective antihypertensive drugs. This study was done to find the effects of two different angiotensin receptor blockers on various biochemical markers in type-2 diabetes mellitus patients. Methods This was a prospective interventional study, comparing two ARBs Azilsartan and telmisartan, involving 76 patients with type 2 diabetes mellitus and hypertension. Results Both drugs controlled blood pressure equally. The study showed that improvement in fasting plasma glucose was more with Azilsartan as compared to Telmisartan but their mean difference is not statistically significant (p > 0.05). The improvement in post-prandial plasma glucose and HbA1C was more with Telmisartan as compared to Azilsartan but only mean HbA1C was statistically significant (p < 0.05). Conclusions Telmisartan has a better impact on HbA1c reduction than Azilsartan, as a part of the pleotropic effect of ARBs.